Imaging anatomy. - Saremi, Farhood (Thieme, 2021)
"This atlas provides high-quality multiplanar and volumetric color-coded imaging techniques utilizing CT, MRI, or angiography, supplemented by cadaveric presentations and color drawings that best elucidate each specific anatomic region. Twenty-one chapters with concise text encompass thoracic wall, mediastinum, lung, vascular, and cardiac anatomy, providing readers with a virtual dissection experience. Many anatomical variants along with pathological examples are presented"-- Provided by publisher
Keywords: Diagnostic imaging -- Atlases.; Lungs -- Anatomy -- Atlases.; Mediastinum -- Anatomy -- Atlases.; Heart -- Anatomy -- Atlases.; Lung -- anatomy & histology; Lung -- diagnostic imaging; Mediastinum -- anatomy & histology; Mediastinum -- diagnostic imaging; Heart -- anatomy & histology; Heart -- diagnostic imaging; Diagnostic Imaging -- methods; Imagerie pour le diagnostic -- Atlas.; Poumons -- Anatomie -- Atlas.; Médiastin -- Anatomie -- Atlas.; Cœur -- Anatomie -- Atlas.; Diagnostic imaging; Heart; Lungs; Mediastinum; Atlas; atlases.; Scientific atlases; Atlases; Anatomical atlases; Atlases.; Atlas.